Upaya Meningkatkan Pemahaman Siswa terhadap Materi Pertumbuhan dan Perkembangan Makhluk Hidup di Kelas V Sekolah Dasar - Hepta Aprilliana; Devi Puspita; Cicha Listiani; Yyadi Heryadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study was motivated by the low level of understanding among fifth-grade elementary school students regarding the topic of growth and development in living beings. This condition affected their learning outcomes, which had not yet met the Minimum Mastery Criteria. The aim of this research was to improve students’ understanding through the application of active and contextual learning approaches. The method used was classroom action research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were fifth-grade students from a public elementary school. Data were collected through observation, interviews, and concept understanding tests. The results showed a significant improvement in students’ comprehension after the learning interventions. The average student scores increased progressively from the pre-action phase to the end of the second cycle. These findings indicate that employing appropriate learning strategies aligned with the nature of the material and students’ needs can effectively enhance science concept understanding at the elementary level. The implication is that teachers should be more innovative in selecting instructional methods that actively engage students to create meaningful and enjoyable learning experiences.